Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy: Phenotypic and mutational spectrum in patients from mainland China. (3rd August 2015) - Yin, Xinzhen; Wu, Dingwen; Wan, Jinping; Yan, Shenqiang; Lou, Min; Zhao, Guohua; Zhang, Baorong
<x xml:space="preserve">Abstract</x> Aims: To analyze the NOTCH3 gene mutations in patients from mainland China clinically suspected to have cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and evaluate large intracranial arteries in CADASIL patients. Methods: We performed clinical, neuroimaging and NOTCH3 gene (exons 2–23) examinations in 47 subjects from 34 families. Large intracranial arteries were assessed using magnetic resonance angiography (MRA) in 19 cases with NOTCH3 gene variants. Results: Screening of exons 3 and 4 identified six different known mutations in eight families and two novel mutations in two families. Further screening of the remaining exons identified p.R1175W, a variant of unknown significance. The incidence of NOTCH3 mutations was 29.4% (10/34). Five cases with NOTCH3 mutations showed intracranial atherosclerosis. One patient developed cerebral infarction due to left middle cerebral artery occlusion (M2 segment). Conclusions: The NOTCH3 mutation spectrum in our group was diverse and consistent with those in Caucasians but differed from those in Korea and Taiwan. The screening strategy used in Caucasian populations can be applied to mainland Chinese patients. Atherosclerosis of the large intracranial arteries involvement does not exclude CADASIL diagnosis.